Study of the Mobile Phone Technology in Creating Awareness among Small Farmers of Sindh Province - Har Bakhsh Makhijani; Muhammad Ismail Kumbhar; Shuhabuddin Mughal; Hameeda Masood Shah; Naseer Ahmed Abbasi (Journal of Basic & Applied Sciences, 2015)
Information and communication knowledge have played a positive role in different segments of the society such as in agriculture education and community development. Now a days most of the farmers are using these technologies especially mobile phones which have given a fruitful result to community. This study was conducted in Sindh Pakistan and survey was conducted in district Jamshoro Taulka Manjhand. Total two hundred respondents were randomly selected for data collection. The study indicated that 90% of the respondents possessed their personal mobile phones and 70% of the respondents utilized mobile for communication with their friends. While 75% of the were of the opinion asked that mobile phones have made their lives easy. However, the results showed that 72% did not contact with any agriculture officer and similarly not contacted with customers to sell their product. Furthermore, study revealed that 74.5% of the respondents replied that they utilize internet on mobile phones. Overall result indicated that farmers are not getting any benefit or increase their income, save time and energy by using the mobile phones in their places.